TINJAUAN ATAS APARATUR SIPIL NEGARA (ASN) YANG MENGUNDURKAN DIRI PADA SALAH SATU LEMBAGA PEMERINTAH NON KEMENTERIAN (LPNK) - Rafly Nur Faizi; Candra Sigalingging (Mount Hope Management International Journal, 2024)
This research examines the increasing phenomenon of resignations from State Civil Apparatus (ASN) in one of the non-ministerial government institutions (LPNK). This research applies a qualitative descriptive method to identify the causes of resignation and its impact on organizational performance and the quality of public services. Research findings show that ASN resignations are dominated by employees aged 20-40 years, especially from the millennial generation who are looking for flexibility and freedom in work. The majority of ASNs who resigned had a service period of 6-15 years and served as first and junior functional experts. The main reason for resignation is the desire to be with family and look for work opportunities elsewhere. The dense workload and lack of flexibility in managing working time, such as the Work from Home (WFH) and flexi time methods not being implemented, also influenced the ASN's decision to resign. It is recommended that non-ministerial government agencies adopt more flexible policies regarding work placement and working time arrangements, as well as creating a work environment that supports career development and work-life balance. With these steps, it is hoped that one of the non-ministerial government agencies can maintain competent ASN and reduce the number of resignations.